Evolution of Jean-Léon Gérôme's colour schemes - Wu, Jamin Jiamian (Nanyang Technological University, 2023)
This research investigates the evolution of Jean-Léon Gérôme’s colour schemes across different periods of his artistic career, from the 1840s to the early 1900s. Several changes were observed in his approach to painting, influenced by events such as the introduction of photography, travel access to the Orient lands, the demise of history painting, experimentation with wide landscape formats, and mass production and consumption. These events rose from the scientific revolution, in which numerous theoretical light and colour frameworks, and chemistry advancements in synthesising new and chromatic colour pigments and dyes, were developed. The newly acquired colour science and availability of chromatic pigments expanded the painters’ colour knowledge and possible practical colour range. It assisted artists such as Gérôme, who managed to render scenes in more chromatic colours and photorealistic outdoor lighting, which assisted him in developing his signature style. Gérôme’s painting repertoire spans multiple styles and subject matter, such as Neo-Grec, history painting, and Orientalism. Unfairly categorised as primarily an Orientalist, discussions on his artworks have been mostly relegated to the negative connotations surrounding Orientalism. Orientalist art, which Gérôme has been generally categorised under, has been strangely left out from discussion of its technical innovations, despite the apparent progression in colour applications the Orientalist artists have shown. An artist of Gérôme’s established career achievements and stature and the long list of future well known students’ pedigree should warrant lengthy studies on his artistic techniques. The dearth of information about Gérôme’s technicalities shows that his artworks across this period need to be studied. By studying Gérôme’s colour schemes, new information on his progression across this period may provide a new perspective on understanding colour applications and colour theory development. This research discovered that Gérôme had multiple developments in his colour schemes. Patterns of new colour experimentation, refinement and objectives are observed. One apparent development discovered is his use of a wide range of greens to create more complex compositions. The colour maps suggest that his expanded use of green hues started at a relatively precise point in his career, around 1870, when he started to depict Turkish subject matter and objects. 10 The results from the above analysis can provide more insights into Gérôme’s art or Orientalist art. The set of methods constructed for this research can also be applied to analyse any other artist or art movement. Both the above research outputs can be useful for practising artists who are interested in learning about colour schemes. In this research, “colour scheme” refers to the colours used and how they are used for environmental representation and emotional response in a painting. The Munsell Colour System, widely used in various major industries, will be used as the analytical tool to study the colour schemes of Gérôme’s works. The research outcome will add to the knowledge of late 19th-century Orientalist art and the understanding of colour application for the current applied-art industries such as digital concept art and cinematography.